Nilai Dosis Radiasi pada Pemeriksaan Radiografi Abdomen AP - Isnoviasih, Susi Tri; Aryani, Asri Indah; Bequet, Angga Yosainto (Jurnal Imejing Diagnostik (JImeD), 2024)
Background: Abdominal radiography examination is one of the examinations that is routinely carried out on the abdominal area to diagnose abnormalities in the abdominal area using radiation. In the stomach area there are gonads which are organs that are sensitive to radiation. The X-rays that come out of the X-ray tube are polyenergy, that is, they are composed of low energy x-ray, medium energy x-ray and high energy x-rays. Low energy x-rays have no benefit on the radiographic image information produced, but only increase the radiation dose on the skin surface. The additional x-ray filter is able to prevent low-energy x-rays from hitting the patient. The aim of this study is to determine the difference in the dose of radiation during the abdominal examination between the use of an additional filter and the use of an additional filter without an additional filter.Methods: The research was carried out at the Radiology Unit of the Prof. Dr. Margono Soekarjo Regional Hospital, Purwokerto and the Purwokerto Radiology Study Laboratory, Poltekkes Semarang with a sample of 50 samples with variations in the use of filters including 0 mm, 1 mm Al + 0.1 mm Cu, and 1 mm Al + 0.2 mm Cu and 2 mm Al. The data measured is the radiation dose On the surface of the Gonad organ's skin.Results: The results of measuring the average dose to the skin surface of the gonad organ are 180.26 mSv on a 0 mm Al filter, 83.32 mSv on a 1 mm Al + 0.1 mm Cu filter, 58.32 mSv on a 1 mm Al + 0 filter, 2 mm Cu and 119.49 mSv on a 2 mm Al filter. The greatest reduction in radiation dose occurred when using an additional filter of 1 mm Al + 0.2 mm Cu, amounting to 68% of that without using an additional filter. The decrease in the use of other filters was 54% when using an additional filter of 1 mm Al + 0.1 mm Cu and 34% when using an additional filter of 2 mm Al. The statistical tests showed there was a difference in the radiation dose during abdominal examination between using an additional filter and without using an additional radiation filter with a significance value of 0.000 (p-value < 0.05).Conclusions: There is a difference in radiation dose during abdominal examination between using an additional filter and without using an additional filter with a significance value of 0.000 (p-value < 0.05).